Cryptosporidium and Cyclospora infection transmission by swimming - Ghimire, TR; Ghimire, LV; Shahu, RK; Mishra, PN (Journal of Institute of Medicine Nepal, 2010)
Cyclospora and Cryptosporidium are obligate, intracellular, coccidian protozoa that cause selflimited diarrhoea in immunocompetent and prolonged diarrhoea in immunocompromised patients. This is the first case of coccidia infection acquired after swimming in a swimming pool in Nepal. This study describes the chronological evidence of these coccidia infections in a Nepalese swimmer with the possible epidemiological link of the environmental contamination in swimming pools in Kathmandu. It represents an important public health issue among the urban areas of the world. DOI: http://dx.doi.org/10.3126/joim.v32i1.4003 Journal of Institute of Medicine, April, 2010; 32:1 pp.43-45